Analysis of Unsecured Loans (KTA) in terms of the Prudential Banking Principle - Noer Dini Camelia; Rifkah Romizah; Iftitah Dian Ukhrowi; Ihsyan Jani Syamsi (LEGAL BRIEF, 2022)
Bank is an intermediary institution that accommodates public funds and distributes them in the form of credit. One of the credit loan facilities provided by banks is Unsecured Loans (KTA). The existence of Unsecured Credit (KTA) causes banks to be deemed not to carry out their obligations to apply one of the principles in banking, namely the Prudential Principle as contained in the provisions of Article 8 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking. Unsecured Credit (KTA) is a form of bank facility that is considered very risky because it does not meet the credit principles that are guaranteed by banks in providing loans, known as the "5C" principle, namely Character, Capital, Capacity, Collaterals and Conditions of Economy. This study aims to analyze the Prudential Principle, especially in the provision of Unsecured Loans (KTA). This research is normative legal research with a statutory approach. Based on Article 8 of Law Number 10 of 1998 Concerning Amendments to Law Number 7 of 1992 Concerning Banking, banks are required to pay attention to the conditions in granting credit, including believing debtors have good intentions and the ability to pay, and to observe the credit principle "The 5 C's Analysis of Credit." The "5C" credit principle includes collateral as an additional guarantee, thus it is not required in credit provision. Unsecured Credit does not contradict the concept of caution in credit payments provided the bank is convinced the credit will be returned.